Economic Evaluation of Interventions to Increase Colorectal Cancer Screening at Federally Qualified Health Centers. Issue 6 (November 2020) - Tangka, Florence K. L.; Subramanian, Sujha; Hoover, Sonja; DeGroff, Amy; Joseph, Djenaba; Wong, Faye L.; Richardson, Lisa C.
The Centers for Disease Control and Prevention (CDC) has a long-standing commitment to increase colorectal cancer (CRC) screening for vulnerable populations. In 2005, the CDC began a demonstration in five states and, with lessons learned, launched a national program, the Colorectal Cancer Control Program (CRCCP), in 2009. The CRCCP continues today and its current emphasis is the implementation of evidence-based interventions to promote CRC screening. The purpose of this article is to provide an overview of four CRCCP awardees and their federally qualified health center partners as an introduction to the accompanying series of research briefs where we present individual findings on impacts of evidence-based interventions on CRC screening uptake for each awardee. We also include in this article the conceptual framework used to guide our research. Our findings contribute to the evidence base and guide future program implementation to improve sustainability, increase CRC screening, and address disparities in screening uptake.